2008
DOI: 10.1128/jvi.02202-07
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Methyltransferase Catalyzes Two Methylations of the Viral RNA Cap through a Substrate-Repositioning Mechanism

Abstract: Flaviviruses encode a single methyltransferase domain that sequentially catalyzes two methylations of the viral RNA cap, GpppA-RNA3m 7 GpppA-RNA3m 7 GpppAm-RNA, by using S-adenosyl-L-methionine (SAM) as a methyl donor. Crystal structures of flavivirus methyltransferases exhibit distinct binding sites for SAM, GTP, and RNA molecules. Biochemical analysis of West Nile virus methyltransferase shows that the single SAMbinding site donates methyl groups to both N7 and 2-O positions of the viral RNA cap, the GTP-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
176
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(198 citation statements)
references
References 37 publications
18
176
1
Order By: Relevance
“…Currently, the test is being further optimized to use lower enzyme and substrate concentrations. Interestingly, it was shown that sinefungin inhibits WNV replication with an EC 50 of 23 mM and a therapeutic index of 167 (Dong et al, 2008a). Thus, although it has also been reported to inhibit mammalian MTases (Chrebet et al, 2005;Osborne et al, 2007), sinefungin or its analogues might show specificity towards selected viral AdoMet-dependent MTases depending on 29O-methyltransferase activity of dengue virus NS5 subtle differences in their AdoMet-binding sites.…”
Section: Inhibition Of Ns5mtase DV 2 §O-mtase Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the test is being further optimized to use lower enzyme and substrate concentrations. Interestingly, it was shown that sinefungin inhibits WNV replication with an EC 50 of 23 mM and a therapeutic index of 167 (Dong et al, 2008a). Thus, although it has also been reported to inhibit mammalian MTases (Chrebet et al, 2005;Osborne et al, 2007), sinefungin or its analogues might show specificity towards selected viral AdoMet-dependent MTases depending on 29O-methyltransferase activity of dengue virus NS5 subtle differences in their AdoMet-binding sites.…”
Section: Inhibition Of Ns5mtase DV 2 §O-mtase Activitymentioning
confidence: 99%
“…We tested various AdoMet analogues (see Methods), among them molecules with proven viral mRNA cap MTase inhibition capacity, such as the reaction product AdoHcy (Pugh & Borchardt, 1982) and sinefungin (Dong et al, 2008a;Li et al, 2007;Pugh et al, 1978), but also molecules inhibiting other AdoMet-dependent MTases, such as 59-S-isobutylthio-59-deoxyadenosine (SIBA), 3-deaza-adenosine (Kloor et al, 2004) and 59-deoxy-59-methylthio-adenosine (MTA) (Woodcock et al, 1983), or simply analogues of adenosine (29,39,59-tri-O-acetyl-adenosine) and AdoMet. We also used three GTP analogues: broad-spectrum antiviral ribavirin and its triphosphate, as well as 5-ethynyl-1-b-Dribofuranosylimidazole-4-carboxamide) (EICAR) triphosphate.…”
Section: Inhibition Of Ns5mtase DV 2 §O-mtase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been generally assumed that like cellular RNAs, many viral RNAs have a 5′ m7G cap, and that viruses either use the cellular capping machinery (e.g., viruses that replicate in the nucleus) or encode their own capping enzymes (e.g., viruses that replicate in the cytoplasm) (15,16). Interestingly, there is a surprisingly diverse range of cap modifications; for instance, Mimivirus, a large DNA virus of amoeba, encodes an RNA cap guanine-N2 methyltransferase that hypermethylates the viral RNA cap (17); influenza virus "snatches" caps from cellular mRNAs (18,19); West Nile fever virus has two methyl additions on its RNA cap (20); Sindbis virus produces mRNAs that have dimethylguanosine and trimethylguanosine caps [hypermethylated caps/m 2,2,7 G caps (21)]; and Semliki forest virus late mRNAs also have hypermethylated caps (22). On the other hand, poliovirus, encephalomyelitis virus, foot and mouth disease virus, and Calici virus are examples of viral RNAs lacking 5′ caps (11,23), and there is limited in vitro evidence that HIV-1 RNAs are capped (24,25).…”
mentioning
confidence: 99%
“…In the case of chlorella virus, the RTPase, GTase and (Hodel et al, 1996); in West Nile virus (WNV), NS5 protein has only one MTase domain catalysing both N 7 -MTase and 29-O-MTase reactions through a substrate-repositioning mechanism (Dong et al, 2008;Ray et al, 2006;Zhou et al, 2007), whereas in the case of BTV, protein VP4 is not only responsible for the GTase and RTPase activities (Martinez-Costas et al, 1998), but also has MTase activity .…”
Section: Cytoplasmic Polyhedrosis Virus Belongs To the Genusmentioning
confidence: 99%